The Eye Of The I From Which Nothing Is Hidden - Hawkins, David R
This is the second volume of a trilogy that began with Power vs. Force and is completed by the publication of the third volume entitled I: Reality and Subjectivity.The Eye of the I (which calibrates at 950) is more advanced than Power vs. Force (which calibrates at 850) and brilliantly reveals the very core of the spiritual process critical to the state of Enlightenment.The intrinsic power of the information provided in this startling classic is sufficient of itself to elevate the consciousness of the reader. This likelihood has been anticipated and provided for by preparatory recontextualizations. Included are verbatim dialogues with advanced students, instructions and explanations that illuminate the spiritual teachings. The Eye of the I is a brilliant work that dissolves the barriers between the known and the unknown, between science and spirituality, and between the Newtonian linear paradigm of the ego and the nonlinear reality of Enlightenment. With the resolution of the self, the Self shines forth and reveals one's true identity.